LocTrackJINQS: An extensible location-aware simulation tool for multiclass queueing networks - Horng,TC; Anastasiou,N; Field,T; Knottenbelt,W (Electronic Notes in Theoretical Computer Science, 2011)
This paper presents LocTrackJINQS, a flexible and extensible spatio-temporal simulation tool for systems that involve the flow and processing of customers at multiple service centres. Developed based on the multi-class queueing network simulation package JINQS, LocTrackJINQS retains the abstract model specification power of JINQS while providing additional low-level models of entity movement. Besides traditional performance metrics, LocTrackJINQS produces as output a trace of each entity's location in the system over time. It can thus be used to generate synthetic location tracking data for location-based research or applications. © 2011 Elsevier B.V.